Evaluation of Human Urinary N-acetyl beta – D- glucosaminidase index in children with urinary tract anomalies - Ali, Raghad J.; Al-Obaidi, Firyal H.; Ahmed, Nariman F.; Hummdy, Hussein (Journal of the Faculty of Medicine Baghdad, 2015)
Background: The kidneys perform glomerular filtration, tubular reabsorption, and tubular secretion and the study of urinary excretion of some enzymes considered as a sensitive test for the detection of early stages of renal disease, particularly N-acetyl-β-D-glucosaminidase (NAG) which is a hydrolytic lysosomal enzyme present in the epithelial cells of the proximal convoluted tubule. Increased urinary NAG due to tubular damage could be used as a marker by a simple non invasive test for prediction of urinary tract problems like pelviureteric junction(PUJ) obstruction ,vesicouretric reflux(VUR) and pyelonephritis. Objectives: to assess urinary NAG/ urinary creatinine (NAG/ Cr) ratio in children with different urinary tract anomalies and compare it with normal healthy children. Patients and Methods: A prospective study was conducted from November, 2012 to April, 2013. Urine samples were collected from 51 patients with Urinary tract problems, and 40 healthy children as a control group, their age range (1month-13years). Children were admitted to Pediatric nephrology department, Children Welfare Teaching Hospital / Medical City Complex, Baghdad, Iraq. The Glomerular filtration rate was in normal range in all of them. Urine samples were tested for NAG by (ELISA,Cusabio ,China) while, both Serum creatinine (S-Cr) and urine creatinine (U-Cr) were estimated by Jaffe’s kinetic method. Results: The current results revealed that NAG/creatinine index was significantly higher in patients with vesicoureteral reflux, Pelviureteric junction obstruction and pyelonephritis in comparison with cystitis. Conclusions: The assessment of urinary NAG could be considered as a useful marker in prediction of the vesicoureteral reflux, hydronephrosis secondary to Pelviureteric junction obstruction .Urinary NAG is elevated in children with pyelonephritis and it can be considered as a further criterion in the diagnosis of upper urinary tract infection.